Comparison of physical performance among Brazilian elite soccer players of different age-categories - Kobal, R.; Loturco, I.; Gil, S.; cal Abad, C. C.; Cuniyochi, R.; Barroso, R.; Tricoli, V. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to compare the physical performance (i.e., strength, power, speed and endurance) between Brazilian elite soccer players from different categories of the same club: professionals (PRO), under-20 (U-20), and under-17 (U-17).